Development of Mobile Learning Platform as A Learning Supplement for Tafsir Hadith Course - Mochammad Rizal Ramadhan; Achmad Hamdan (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This study aims to: 1.) Design a mobile learning platform for the Tafsir Hadith course; 2.) analyzing the development of a mobile learning platform in the Tafsir Hadith course; 3.) analyzing the implementation of the mobile learning platform in the Tafsir Hadith course; 4.) analyzing the evaluation of the mobile learning platform in the Tafsir Hadith course. The development model used is the 4D model developed by Thiagarajan, which includes define, design, develop, and distribution. The results showed that the product-based test based on expert and media expert judgments was obtained at 84.16% and 83.33% in the feasible category. Then the results of the limited trial were obtained at 81.61% and the field trial at 88.33% in the very feasible category. Therefore, it can be said that the development of a mobile learning platform in the Tafsir Hadith course is very suitable to be used as a learning supplement.